2012
DOI: 10.2190/om.65.2.b
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Grief Interventions: Eras of Witnessing with Families

Abstract: This article describes research that was conducted to articulate interventions with families experiencing grief. Using an interpretive methodology framed by philosophical hermeneutics allowed for a depth of understanding of these therapeutic conversations. The research findings offer explanations of the role of time in relation to grief, particularly the timing of interventions, and describe the significance of working with multiple family members during therapeutic interventions. This research was unique in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…It has been noted that most intervention work has been only theoretical, e.g. focusing upon the manner in which family systems theory can inform research, with little explanation and/or empirical validation for reported effects on families who have experienced some form of therapy (Thirsk, 2009;Thirsk & Moules, 2012).…”
Section: Therapeutic Implications Of a Family Systems Approach To Grimentioning
confidence: 99%
See 2 more Smart Citations
“…It has been noted that most intervention work has been only theoretical, e.g. focusing upon the manner in which family systems theory can inform research, with little explanation and/or empirical validation for reported effects on families who have experienced some form of therapy (Thirsk, 2009;Thirsk & Moules, 2012).…”
Section: Therapeutic Implications Of a Family Systems Approach To Grimentioning
confidence: 99%
“…what does the family need at a particular time. Thus, understanding the family's grief should be understood in terms both short-term and long-term time frames, stressing what family members can do to help one another during therapy (see Moules, Simonson, Fleiser, Prins, & Glasgow, 2007;Thirsk & Moules, 2012). Underscoring the family systemic nature of grief is the observation that What was most striking with these families was how different the clinical work would have been had they been seen individually and had there been a focus on their emotional and psychological state .…”
Section: Therapeutic Implications Of a Family Systems Approach To Grimentioning
confidence: 99%
See 1 more Smart Citation
“…Instances such as these, when sessions were not seen as useful, also have something to offer in terms of understanding nursing practice with families. One interpretation of why the sessions were not helpful was related to timing, as has been reported elsewhere (see Thirsk & Moules, 2012).…”
Section: Diannementioning
confidence: 74%
“…Bereaved families’ unique configurations, needs, capacities and meaning‐making strategies are of interest (Gilbert, , Nadeau , Berger & Weiss , Davis et al ., ). While a focus on what constitutes age‐normative family functions continues to abound, it is increasingly appreciated that manifold ways of living as a family and grieving meaningfully co‐exist (Hedtke & Winslade , Nadeau , Neimeyer , Thirsk & Moules ).…”
Section: Introductionmentioning
confidence: 99%